Epidemiology of primary gonarthritis in patients aged over 40 years - Jarecki, Jaromir (Polish Journal of Public Health, 2009)
Introduction. Arthritis is the most common joint pathology. It depends on aging and gender and causes pain and general disability of older people. Aim. The aim of the study is the assessment of patients aged over 40 years with primary gonarthritis in developing gonarthrosis. Materials and methods. The studied group covered 51 patients with primary gonarthrosis. During evaluation of the patients’ questionnaires, radiological scales and clinical examination were used. Results. Mean age was 61.76 years. In the studied group women prevailed (38 versus 13 men). Twenty two (22) people lived in the cities and 19 in rural area. The majority of studied patients did not have a job. Mean body mass index (BMI) was 30.3. Overweight was present in 82% of the patients. More frequently the changes were observed in the right knee joint. Almost half of the patients used sticks. Discussion. Arthritis is connected with general aging process. It remains unclear, if the primary defect is located in cartilage or subchondral bone. The disease is more frequent in women, which may be related to hormonal changes. In the studied group overweight was present in 82% of the patients. General metabolic disorders may infl uence the progression of the disease. Another hypothesis is with relation to a change in mechanical axis of the lower limb. The development of arthrosis is connected with genetic predisposition. Conclusions. Primary gonarthrosis is observed in elder women. Patients are treated medically for prolonged period of time. Complex instability of the knee, decreasing range of motion and swelling are often observed. Varus deformity of the knee prevails.